PENGARUH KECANGGIHAN TEKNOLOGI INFORMASI DAN JIWA KEWIRAUSAHAAN TERHADAP KUALITAS INFORMASI AKUNTANSI - Tiara Pratistha Sari, Ida Ayu Komang; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2017)
The quality of accounting information is part of the measurement of the effectiveness of an information system. This study aimed to examine the effect of sophistication of information technology and the entrepreneurial spirit of the quality of accounting information. Research was conducted on students in the entrepreneurial community in the Youth Entrepreneurial Faculty of Economics and Business, University of Udayana. The number of samples obtained by 55 samples by purposive sampling technique. Data were collected using a questionnaire. The analysis technique used is multiple linear regression analysis. The result of this study indicate that the sophistication of information technology and entrepreneurial spirit positive effect on the quality of accounting information. Relations sophistication of information technology with the quality of accounting information is the process of assessing the financial statements still manually requires a long time, now using accounting software in the modern era to help the inspection easier work.
Keywords: Sophistication of Information Technology, Entrepreneurial Spirit, Quality of Accounting Information